Are the Latent Variables in Time-Varying Expected Returns Compensation for Consumption Risk? - Ferson, Wayne E (Journal of Finance, 1990)
Multibeta asset pricing models are examined using proxies for economic state variables in a framework that exploits time-varying expected returns to estimate conditional betas. Examples include multiple consumption-beta models and models where asset returns proxy for the state variables. When the state variables are not specified, the tests indicate two or three time-varying expected risk premiums in the sample of quarterly asset returns. Conditional betas relative to consumption generate less striking evidence against the model than betas relative to asset returns, but both the consumption and the market variables fail to proxy for the state variables.